Identity in conflict the struggle between Esau and Jacob, Edom and Israel - Assis, Eliyahu (Eisenbrauns, 2016)
"No nation has been subjected to a wider range of biblical attitudes and emotions than Edom. In some sources, Edom is perceived as Israel's brother; in many others, the animosity toward Edom is tremendous. The book of Genesis introduces Isaac, his wife Rebecca, and their twin sons, Esau and Jacob. Rivalry between the brothers emerges even before their birth and escalates over the course of their lives. The question of which son should be favored also causes tension in the parents' relationship, and most of the Genesis text concerning Isaac and Rebecca revolves around this issue. The narrative describes the fraternal conflict between Jacob and Esau at length, and many hold that this description is a reflection of the hostility between Edom and Israel. However, the relationship between the brothers is not always depicted as strained. The two fold relationship between the brothers in Genesis--brotherhood and fraternity coupled with hatred and rivalry--introduces a dichotomy that is retained throughout the Hebrew Bible. In this monograph, Assis elucidates the complex relationship between Edom and Israel reflected in the Bible, to attempt to clarify the source of this complexity and the function that this relationship serves in the various biblical texts and Israel's early history. He shows how this relationship plays an important role in the formation of Israel's identity, and how the historical interaction between the nations influenced the people's theological conception, as reflected in prophetic literature, poetry, and biblical narrative"--
Description based on print version record
Keywords: Jacob -- (Biblical patriarch); Esau -- (Biblical figure); Bible -- Genesis -- Criticism, Narrative; Bibel; Twins in the Bible